Analisis Biaya Produksi, Harga Jual, Dan Titik Impas Sebagai Alat Perencanaan Laba Pada Usaha Nelayan CV. PUTRA LEO - Sa'anana, Resti NPW, Ahmad Mardalis, S.E.,M.B.A (2015)
This study aims to determine the factors that influence profit planning at CV. Son Leo during February 2014-July 2015 to memprekdisikan. The authors apply the analysis of break-even point in doing this research. It is based on the concept that explains the break-even point between costs, volume of sales and profits. In analyzing the breakeven point for analyzing the linkage of production costs, and selling prices of products sold in achieving the BEP. The method used in this study is documentation, literature, and interviews. The research location and sample selected intentionally (purposive) that the fishing effort CV. Son Leo in the village Bendar Juawana District of Pati regency. Data analysis method used is descriptive, namely: 1) the calculation of the break-even point in units and rupiah, 2) analysis of profit planning. Results of this study found that from February 2014-July 2015 with the attainment of the advantages of the biggest break-even analysis is on KM. Shining son Leo, while achieving the advantage of the lowest break-even analysis is on KM. Son Leo Abadi of the break-even point can we know the profit planning with expected profits by 10% .Therefore profit planning at CV. Son Leo should use the calculation of fixed costs and variable costs for menegtahui break-even point. With decision-making, management better use of production costs to differentiate fixed costs and variable costs. Thus the company the company should be very concerned about the costs that come out in order to suppress any fees that come out with the total income earned. Keywords: Production Costs, Selling Prices, and Break-Even